Monogenean fauna (Platyhelminthes, Monogenea) of Trachelyopterus galeatus (Linnaeus, 1766) in a region of the Brazilian western amazon - Damaceno Bezerra, Carine (2025)
The present study evaluated the Monogenea fauna parasitizing Trachelyopterus galeatus Linnaeus, 1766 (Cangati) and investigated the influence of environmental and morphometric factors on the abundance of these parasites. Six species of monogeneans were identified, with Ameloblastella sp. and Cosmetocleithrum sp. being the most prevalent and having the highest mean intensity. Ameloblastella sp. stood out significantly compared to the other species, suggesting greater adaptive and competitive efficiency. It was observed that 46% of the fish harbored two species of Monogenea, while 10% harbored four or five species, indicating the coexistence of these parasites. Despite variations in host weight, length, and condition factor, these characteristics showed no significant relationship with the abundance of Monogenea, suggesting that individual body factors are not determinants of the infestation pattern. On the other hand, a strong influence of environmental variables such as chlorophyll content, water temperature, and dissolved oxygen was identified on the abundance of these parasites. Favorable environmental conditions, such as higher temperatures and eutrophication, appear to promote the proliferation of Monogenea by enhancing reproduction and facilitating contact between hosts. The findings of this research expand the understanding of parasitic ecology in the Amazon, highlighting the importance of monitoring environmental factors to predict and mitigate parasitic outbreaks in freshwater fish.